Optimizing Gold Installment Product Marketing to Increase Customer Engagement in Islamic Non-Bank Financial Institutions - Habibah, Siti Habibatur Rahma; Dimas, Muhammad Dimas Firmansyah; Oluwatosin, Yahya Isiaq (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The increasing public interest in gold investment and the rapid digitalization of financial services have intensified competition among non-bank financial institutions in Indonesia. However, previous studies have predominantly focused on general investment behavior and have paid limited attention to hybrid marketing strategies for gold installment products at the operational branch level. This study aims to analyze the effectiveness of the 7P marketing mix strategy implemented by PT Pegadaian UPC Tamanan in increasing customer engagement and customer growth for the Gold Installment (Cicil Emas) product. This research employed a qualitative descriptive approach using in-depth interviews, observation, and document analysis. Ten informants consisting of branch managers, marketing staff, customers, and community members were selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model and validated through source and method triangulation. The findings reveal that the integration of affordable installment schemes, digital promotion through Pegadaian Digital Service (PDS), and interpersonal relationship-based services significantly enhances customer trust, investment literacy, and customer acquisition. The study also identifies that customers perceive the Gold Installment product not merely as a financing facility but as a mechanism for financial security and long-term asset protection amid economic uncertainty. The theoretical contribution of this study lies in extending the 7P marketing mix framework by integrating financial inclusion and investment literacy dimensions within hybrid financial marketing. Practically, the study offers strategic insights for non-bank financial institutions in developing adaptive marketing models that combine digital technology, social interaction, and financial education to strengthen competitiveness and sustainable customer engagement in semi-rural communities.